Boredom, apocomy, emptiness — the diseases of the contemporary human being or noogenic neurosis in the view of V.E. Franki? - Buksik, Dariusz (Studia Psychologica: Theoria et praxis, 2009)
Existential psychology defines a human being in the context of his existence. It searches for something which constitutes him, which allows him to develop his psyche, grow up and become mature. On the other hand it also signifies the moments which in a certain way lead to the pathology of human existence. These are factors which disturb normal and healthy functioning and at the same time contribute to “disordered functioning: to escape and neurosis”. Reflecting on certain three elements present in the life of a contemporary human being, i.e. emptiness, “apocomy” and boredom, we shall analyse the extent to which they might be of developmental value and when they might become the symptom of neurosis. As shown in the history each age has its own pathology. The meaning of life is a quality which constitutes the most basic need for human existence. Human desires to find one’s own place in the world which is hard to do in existential emptiness. On the one hand the sense of meaninglessness, fear, depression periods, despair, boredom, “apocomy” arises from being too much focused on one’s own needs but on the other hand it also discourages one to do anything and makes one escape.